Demonstration of a quasi-gapless integrated visible light communication and positioning system - Yang, Helin (2019)
In this letter, a quasi-gapless integrated visible light communication and positioning (VLCP) system is experimentally demonstrated for the first time, based on filter bank multicarrier- based subcarrier multiplexing (FBMC-SCM). Compared with orthogonal frequency division multiplexing-based SCM (OFDM- SCM), FBMC-SCM has lower out-of-band interference (OOBI) and therefore requires much smaller guard band (GB) spacing. A low-complexity transmit diversity transmission scheme is adopted here, where all the light emitting diode (LED) lamps transmit the same communication signal.Moreover, phase difference of arrival (PDOA) is applied for positioning. The experimental results show that, in a coverage area of 1.2×1.2 m2 with a height of 2.1 m, the mean position errors using OFDM–SCM and FBMC-SCM for a GB of 0.7 MHz are 10.91 and 6.08 cm, respectively. Moreover, a comparable bit error rate (BER) performance can be achieved for both OFDM–SCM and FBMC-SCM. Due to the negligible GBs when using FBMC-SCM, the effective bandwidth utilization ratio of the integrated VLCP system is improved from 72% to 98% when OFDM-SCM is replaced by FBMC-SCM.